Green Governance Analysis Through Development Food Security Towards Sustainable Green Economy - Satyaguna, Made (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The current food problem cannot be separated from environmental issues developing in Indonesia, ranging from pollution to ecosystem instability, which seriously impacts the economy. Natural disasters to the recent Covid 19 virus pandemic have given a warning signal that ecosystem instability must be a priority not only for the government but also for industry players and the public in building food security. The food estate approach proposed to create food security is believed to meet linear population growth and become a sustainable green economy model, but the failure rate of food estate transformation is relatively high because it has not been able to drive the market economy effectively. Strict regulations and comprehensive guidelines are not the keys to achieving a green economy through a balance of food security and environmental sustainability. A holistic understanding of green governance is needed before pushing food estates to achieve a sustainable green economy.